La investigación etnográfica, un reto para comprender el acontecer del aula - Grace Rojas-Alvarado (Universidad Nacional, Costa Rica, 2002)
These comments center on the area of education and educational research. The latter is a practice which should be part of our daily activities and course programs. The research was conducted using an ethnographic approach with the intention of comprehending the reality of rural areas holistically and reconstructing phenomena in their different contexts as they take place day by day in the classroom. The importance of this type of research is in including protagonist subjects among the main actors of research processes.